Nap to perform? Match-day napping on perceived match performance in professional rugby union athletes - Teece, A. R.; Beaven, M.; Huynh, M.; Argus, C. K.; Gill, N.; Driller, M. W. (International Journal of Sports Science & Coaching, 2023)
Background Daytime napping on match-day is a strategy used by athletes to alleviate sleep debt or to avoid boredom. However, the utilization of pre-match napping and its effect on self-rated performance has not been evaluated in professional Rugby athletes.